Kajian Smart Leadership Pada Kepemimpinan Nabi Muhammad Saw. Dalam Membangun Peradaban Islam - Fatma Sari (LPPM IAIN Sorong, 2022)
This paper examines the leadership of the Prophet Muhammad SAW. in his success in building Islamic civilization which is analyzed using smart leadership theory, namely leadership theory that uses intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) in his leadership. This research uses a literature research method or library research, namely research that prioritizes theoretical and philosophical data processing over empirical in the field. The data sources in this study are books, journal articles, and other sources that support this study. This research concludes that the success of Prophet Muhammad SAW in building Islamic civilization and even he was named a very influential figure with the number 1 order in the world is certainly greatly influenced by the various intelligences he has and optimizes. This shows that from the various intelligences and abilities of the Prophet that the author analyzed have met 3 indicators of smart leadership theory, namely intelligence intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ).